Private placements, cash dividends and interests transfer: Empirical evidence from Chinese listed firms - Zhao, Y.; Xia, X.; Tang, X.; Cao, W.; Liu, X.; Fan, Ying Han (Elsevier, 2015)
In this paper, the relationship between private placements of common stocks and cash dividendsfor Chinese listed firms is investigated. It finds that Chinese listed firms pay more cash dividendsafter private placements than do those that are not involved in placements. Firms with largeshareholders participating in private placements pay more cash dividends than those withoutlarge shareholder participation. These results indicate that the firms controlled by large shareholders have a high propensity for interests transfer in their cash dividend policies.